Pengaruh Disiplin Kerja, Fasilitas Kerja Dan Kompensasi Terhadap Kinerja Pegawai Pada Dinas Pekerjaan Umum Dan Penataan Ruang Kabupaten Serdang Bedagai - Muhammad Harpis; Sandhi Fialy Harahap (CV. Aksara Global Akademia, 2023)
Success in carrying out work duties serving the community can be achieved with the quality of community satisfaction. Improving the quality of performance at the Public Works and Spatial Planning Department of Serdang Bedagai Regency will be achieved by continuously improving the quality of Human Resources and work facilities which are always oriented towards improving the quality and quality of services. The objectives of this research are (1) To analyze the influence of work discipline on the performance of employees at the Public Works and Spatial Planning Department of Serdang Bedagai Regency. (2) To analyze the influence of work facilities on employee performance at the Public Works and Spatial Planning Service of Serdang Bedagai Regency. (3) To analyze the effect of compensation on employee performance at the Public Works and Spatial Planning Service of Serdang Bedagai Regency. (4) To analyze the influence of work discipline, work facilities and compensation on employee performance at the Public Works and Spatial Planning Service of Serdang Bedagai Regency. The population was 70 employees, the sample taken was 64 employees. The data collection methods used were observation, interviews and questionnaires. The results of this research show that partially it can be concluded that work discipline (X1), work facilities (X2) and compensation (X3) have a positive and significant influence on performance (Y) . From the results of this research, it can be concluded that work discipline, work facilities and compensation simultaneously have a significant influence on performance.